L’utilisation du téléphone au volant chez les commerciaux hommes et femmes : habitudes de conduite et prises de risque - Sandrine Gaymard; Besson; T.; Bessin; M.; Rouzier; A.; Carré; J.; Robert; V.; Delaunay; et al. (Perspectives Interdisciplinaires sur le Travail et la Santé)
Phoning while driving is a factor that increases the risk of an accident. Bluetooth is the only equipment currently tolerated by the law in France; there is however no information concerning phone use habits of sales and marketing people while at the wheel. The aim of this survey which was carried out with a French group of male and female sales and marketing people (N=59) was to identify their driving habits and the possible ensuing risks. The results arising from this sample provide new information about occupational risk on the road. Differential aspects can be noted with respect to gender such as road use. Other differences are observed in the management of professional and private life; for example, the respondents had difficulties separating these two areas, thereby exposing themselves to more risks on the road. Several preventive measures could be adopted to reduce these risks.